Investigation for Collapsed Navigation Structures in The Mahakam River Delta by Bathymetry and Sonar - Efendi, Aco Wahyudi (Program Studi Teknik Sipil, 2025)
This study employed an integrated approach of side-scan sonar imaging and bathymetric surveying to precisely locate and characterize collapsed navigation structures within the dynamic Mahakam River Delta. This crucial waterway faces environmental challenges like strong currents and heavy siltation, threatening navigational aid integrity. Accurate identification of these submerged hazards is vital for safe shipping and future infrastructure development. Our findings demonstrated the effectiveness of combining these hydrographic methods to accurately map the seafloor and detect anomalies indicative of collapsed structures. Visual diving confirmed extremely poor underwater visibility, necessitating remote sensing. High-resolution bathymetric surveys successfully identified distinct riverbed anomalies, notably a collapsed structure at 00°50'13.29